Asbestos bodies in bronchoalveolar lavage in the 21st century: a time-trend analysis in a clinical population. Issue 1 (22nd August 2016) - Nuyts, Valerie; Vanhooren, Hadewijch; Begyn, Sarah; Nackaerts, Kristiaan; Nemery, Benoit
Abstract : Objectives: Asbestos bodies (AB) in bronchoalveolar lavage (BAL) can be detected by light microscopy and their concentration is indicative of past cumulative asbestos exposure. We assessed clinical and exposure characteristics, as well as possible time trends, among patients in whom AB had been quantified in BAL. Methods: BAL samples obtained from 578 participants between January 1997 and December 2014 were available for analysis. The processing of samples and the microscopic analysis were performed by a single expert and 76% of samples came from a single tertiary care hospital, allowing clinical and exposure data to be extracted from patient files. Results: The study population (95% males) had a mean age of 62.5 (±12.4) years. AB were detected in 55.2% of the samples, giving a median concentration of 0.5 AB/mL (95th centile: 23.6 AB/mL; highest value: 164.5 AB/mL). The AB concentration exceeded 1 AB/mL in 39.4% and 5 AB/mL in 17.8%. A significant decrease from a geometric mean of 0.93 AB/mL in 1997 to 0.2 AB/mL in 2014 was apparent. High AB concentrations generally corresponded with occupations with (presumed) high asbestos exposure. AB concentrations were higher among patients with asbestosis and pleural plaques, when compared with other disease groups. Nevertheless, a substantial proportion of participants with likely exposure to asbestos did not exhibit high AB counts. Conclusions: This retrospective study of a large clinical population supports the value of counting AB in BAL as a complementary approach to assess past exposure to asbestos.